Implementation contextual factors related to youth advocacy for healthy eating and active living. Issue 5 (27th January 2018) - Bozsik, Frances; Berman, Marcie; Shook, Robin; Summar, Shelly; DeWit, Emily; Carlson, Jordan
Abstract: Healthy eating and active living are critical to youth health and development. Youth advocacy can improve health-related behaviors and environments by empowering youth to act as change agents in their community. This mixed-method study examined implementation contextual factors in relation to implementation success in high school youth advocacy projects targeting healthy eating and active living. Semi-structured interviews were conducted with key informants from each of the 21 participating youth groups. Interviews gathered information on implementation processes, barriers and facilitators, and Implementation Outcomes (Progress, Penetration, Health Impact, Sustainability, and an overall Implementation Success Composite). Interview responses were coded using the Consolidated Framework for Implementation Research (CFIR). Each identified construct was rated for its impact on implementation and ratings were tested for their association with the Implementation Outcomes. Cosmopolitanism (leveraging connections within the community; rated in 20 groups) and Internal Intervention Source (rated in 9 groups) showed consistent moderate/large associations with the Implementation Outcomes and Implementation Success Composite. Other moderate/large associations were outcome specific, with Student Group Leader Engagement, External Change Agents, and Student and Community Needs and Resources also being associated with the Implementation Success Composite. Implementation contextual factors, particularly community-connectedness, group functioning, and internal project idea development are important factors for implementing youth advocacy projects that will reach large numbers of people and be likely to lead to sustained health improvements. Implementation strategies that target these factors need to be developed and tested in partnership with community organizations to maximize success of youth advocacy efforts. Abstract : Youth advocacy groups with favorable group dynamics, community-connectedness, and autonomy had more success implementing impactful projects around healthy eating and active living.